CONTENT ANALYSIS OF STUDENT BOOK“WHEN ENGLISH RINGS A BELL” FOR GRADE VIII JUNIOR HIGH SCHOOL - Theresia Marini Simanjuntak (Institut Agama Islam Negeri Palopo, 2021)
The purpose of this study is to analyze the relationship between inner material student book “ When English Rings a Bell “ for grade VIII SMP with Core Competenicies and Basic Cognitive Field 2013 Curriculu and the realm of psychomotor learning. This research uses descriptive qualitative content analysis as a research method. Data collected from English student book “When English Rings a Bell” for eighth graders of junior high school. The school was written by the writing team of the Ministry of Education and Culture Indonesia. In this study the material in the textbook is classified based on basic competence three as cognitive domain and basic competence four as psychomotor domain. Data is extracted from the data source and entered into checklist table to make comparisons between material in textbooks and the material needed in the 2013 English syllabus for grade VIII students Junior high school.